Induction of long-lasting regulatory B lymphocytes by modified immune cells in kidney transplant recipients - Morath, Christian; Schaier, Matthias; Ibrahim, Eman; Wang, Lei; Kleist, Christian; Opelz, Gerhard; Süsal, Caner; Ponath, Gerald; Aly, Mostafa Gaafa; Alvarez, Cristiam M.; Kälble, Florian; Speer, Claudius; et al. (Journal of the American Society of Nephrology, 2023)
In previous work, the authors demonstrated that kidney transplant recipients developed donor-specific unresponsiveness when they were given a pretransplant infusion of modified donor-derived PBMCs. In this study, they provide evidence that the immunosuppressive properties of these cells persist and the donor-specific unresponsiveness is long-lasting. ...
Online veröffentlicht am 22. September 2022
Gesehen am 28.11.2023